2007
DOI: 10.1073/pnas.0705667104
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic plasticity during mammalian development is directionally dependent on early nutritional status

Abstract: Developmental plasticity in response to environmental cues can take the form of polyphenism, as for the discrete morphs of some insects, or of an apparently continuous spectrum of phenotype, as for most mammalian traits. The metabolic phenotype of adult rats, including the propensity to obesity, hyperinsulinemia, and hyperphagia, shows plasticity in response to prenatal nutrition and to neonatal administration of the adipokine leptin. Here, we report that the effects of neonatal leptin on hepatic gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
243
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(257 citation statements)
references
References 22 publications
9
243
0
5
Order By: Relevance
“…It may act directly or indirectly on those epigenetic processes regulating metabolic canalization. 20 It may be acting by effects on neonatal food intake, but this seems unlikely given that large changes in infant food intake in this model cause only minor modification of the adult phenotype. There is evidence that leptin has effects on the maturation of hypothalamic circuits controlling food intake, 57 and a key question is whether there is a critical period that is accessible in other species, such as the human, that are more mature at birth.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 89%
See 3 more Smart Citations
“…It may act directly or indirectly on those epigenetic processes regulating metabolic canalization. 20 It may be acting by effects on neonatal food intake, but this seems unlikely given that large changes in infant food intake in this model cause only minor modification of the adult phenotype. There is evidence that leptin has effects on the maturation of hypothalamic circuits controlling food intake, 57 and a key question is whether there is a critical period that is accessible in other species, such as the human, that are more mature at birth.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 89%
“…19,20 These are not parentally imprinted genes, supporting a role for nonimprinted epigenetic change in the regulation of developmental plasticity.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 96%
See 2 more Smart Citations
“…The most probable cause of such an effect is the pattern of nutrition during growth and development. It has been suggested that physiological traits are set, often referred to as being 'programmed', by the nutritional environment experienced during early growth (Desai et al 1995;Gluckman et al 2007) as a result of tissue remodelling or changes in cell differentiation, organ growth and/or cell signalling (Bertram et al 2001;McMillen & Robinson 2005;Langley-Evans 2006).…”
Section: Introductionmentioning
confidence: 99%